(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
O. Dovzhenko’s creativity contain many ethno-national thoughts, ideas, images, metaphors, symbols and concepts that have not lost their relevance today. Among them is the Ukrainian national idea, the issue of national-cultural traditions’ continuity, the need for a spiritual foundation for state creation, a balanced ethno-national and humanitarian policy of Ukraine, etc. In fact, from O. Dovzhenko begins the conscious creation of the Ukrainian nation principles as a unique phenomenon and fact of world history. Therefore, the works of O. Dovzhenko need to be read in accordance with the purpose of Ukrainian literature’s studying in school, namely: senior pupils’ humanistic world outlook formation, their involvement by means of art literature to universal and national values, the education of nationally conscious citizens of Ukraine, etc. The article deals with the conceptual dominants as an element of the author’s style of O. Dovzhenko. The author of the article analyzes the artistic forms of ethno-cultural concepts’ realization as an important element of master’s literary works ideologically themed spectrum formation. It is proved that the core ethno-concepts of lot of his works (stories, film stories, dramatic works) and diary entries has become such concepts as «history», «cossack», «zaporozhets», «grave», «Ukraine», etc. It is summarized that the Ukrainian people mentality, its identity and value are represented in the works of the writer with the help of the national concepts.